2016
DOI: 10.4238/gmr.15038400
|View full text |Cite
|
Sign up to set email alerts
|

Genomic identification, phylogeny, and expression analysis of MLO genes involved in susceptibility to powdery mildew in Fragaria vesca

Abstract: ABSTRACT. The MLO (powdery mildew locus O) gene family is important in resistance to powdery mildew (PM). In this study, all of the members of the MLO family were identified and analyzed in the strawberry (Fragaria vesca) genome. The strawberry contains at least 20 members of the MLO family, and the protein sequence contained between 171 and 1485 amino acids, with 0-34 introns. Chromosomal localization showed that the MLOs were unevenly distributed on each of the chromosomes, except for chromosome 4. The great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…Three truncated MLO proteins were identified as putative pseudogenes (Table S2). The number of predicted MLO genes in diploid strawberry agrees with the previous characterization of strawberry MLO genes using the first F. vesca draft genome 25 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Three truncated MLO proteins were identified as putative pseudogenes (Table S2). The number of predicted MLO genes in diploid strawberry agrees with the previous characterization of strawberry MLO genes using the first F. vesca draft genome 25 .…”
Section: Resultssupporting
confidence: 87%
“…This variation was also observed in previous genome-wide MLO studies in other Rosaceous crops such as apple and peach 35 . Phylogenetic analysis grouped strawberry MLO genes into eight different clades, which is consistent with previously classified MLO gene families in diploid strawberry 25 and other Rosaceous crops 35 . Functional MLO genes associated with PM resistance are grouped in clade IV and V for monocots and dicots, respectively 13 .…”
Section: Discussionsupporting
confidence: 86%
“…In this study, it was observed that the number of FvMLO genes and clade numbering of the FvMLO gene family were in contrast to the previously categorized FvMLO genes. Pessina, et al [15] identified 17 FvMLO genes (FvMLO1-FvMLO17) based on sequence information of tomato SlMLO1 amino acid and HMMER programme, whereas Miao, et al [38] reported 20 MLO genes in the strawberry genome (FvMLO01-FvMLO20) using Arabidopsis thaliana and rice MLO protein sequences. Further, the phylogenetic analysis in their studies showed that MLOs were grouped into seven distinct clades.…”
Section: Discussionmentioning
confidence: 99%
“…vesca accession Hawaii 4 [37] allows a comprehensive overview of the strawberry MLO gene family. A few studies have previously reported the identification of FvMLO genes in the F. vesca genome sequence [15,38]; however, the level of expression of these genes in response to disease pressure has not been studied. In the present study, we identified FvMLO genes in the F. vesca genome based on the sequence information of the Prunus americana MLO YW is reported to be susceptible to powdery mildew [39].…”
Section: Introductionmentioning
confidence: 99%
“…The seven-transmembrane domain proteins were homologues of barley mildew resistance locus o (MLO) and were localized in the plasma membrane [71]. The MLO gene family has been reported to be crucial in the resistance to the powdery mildew disease [72]. Calcium-dependent protein kinases have been reported to be present in all plants.…”
Section: Co-expression Analysis Of Pcs Genesmentioning
confidence: 99%